Hα imaging for BeXRBs in the Small Magellanic Cloud - Maravelias, G.; Zezas, A.; Antoniou, V.; Hatzidimitriou, D.; Haberl, F. (2017)
The Small Magellanic Cloud (SMC) hosts a large number of high-mass X-ray binaries, and in particular of Be/X-ray Binaries (BeXRBs; neutron stars orbiting OBe-type stars), offering a unique laboratory to address the effect of metalicity. One key property of their optical companion is Hα in emission, which makes them bright sources when observed through a narrow-band Hα filter. We performed a survey of the SMC Bar and Wing regions using wide-field cameras (WFI@MPG/ESO and MOSAIC@CTIO/Blanco) in order to identify the counterparts of the sources detected in our XMM-Newton survey of the same area. We obtained broad-band R and narrow-band Hα photometry, and identified ~10000 Hα emission sources down to a sensitivity limit of 18.7 mag (equivalent to ~B8 type Main Sequence stars). We find the fraction of OBe/OB stars to be 13% down to this limit, and by investigating this fraction as a function of the brightness of the stars we deduce that Hα excess peaks at the O9-B2 spectral range. Using the most up-to-date numbers of SMC BeXRBs we find their fraction over their parent population to be ~0.002 - 0.025 BeXRBs/OBe, a direct measurement of their formation rate.
Keywords: Astrophysics - Astrophysics of Galaxies; Astrophysics - High Energy Astrophysical Phenomena; Astrophysics - Solar and Stellar Astrophysics; Be; Magellanic Clouds; stars: early-type; stars: emission-line; X-rays: binaries